Adorno e o cinema : possibilidades de uma arte autônoma - Willian Silva de Vasconcellos (2022)
This dissertation intents to explore some immanent tensions in the work of Theodor W. Adorno about the cinema. His reflections gain layers as some aspects of his diagnosis of the cultural industry are reassessed in the years before his death. Cinema finds a prominent place in this process, being the medium that, through determined negation, could contradict and expand the notion of autonomy, as well as the very concept of art.